(untitled) (Revista de Ciências Agroveterinárias, 2024)
In the evaluation of reproductive biotechnologies in pigs in South America, 72 key articles were selected through a comprehensive literature review and a sampling formula was used to ensure representativeness. Data collected from databases such as Scopus and Web of Science, assessed with a Likert scale and a reliability of 70.1% according to Cronbach’s Alpha, reveal that artificial insemination (AI) is the most widely adopted technique, with more than 90% of commercial farms using it. In contrast, embryo transfer (ET) and in vitro fertilization (IVF) show limited adoption, with only 10% of farms applying them due to high costs and low efficiency. Multiple correspondence analysis (MCA) indicates that 55% of publications focus on AI and ET, while only 25% address IVF. The perception of information quality shows that 70% consider articles on AI to be clear, compared to only 40% for IVF. In conclusion, while AI remains prevalent and effective, adoption of ET and IVF faces significant barriers, suggesting an urgent need to improve the accessibility and efficiency of these advanced technologies and strengthen research in less-covered areas.